2010
DOI: 10.1534/genetics.110.122911
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genetic Mapping Points to Different Sex Chromosomes in Sibling Species of Wild Strawberry (Fragaria)

Abstract: Separate sexes have evolved repeatedly from hermaphroditic ancestors in flowering plants, and thus select taxa can provide unparalleled insight into the evolutionary dynamics of sex chromosomes that are thought to be shared by plants and animals alike. Here we ask whether two octoploid sibling species of wild strawberry-one almost exclusively dioecious (males and females), Fragaria chiloensis, and one subdioecious (males, females, and hermaphrodites), F. virginiana-share the same sex-determining chromosome. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
115
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(119 citation statements)
references
References 69 publications
4
115
0
Order By: Relevance
“…As in previous studies (Goldberg et al, 2010;Spigler et al, 2010), we scored male function qualitatively based on the presence or absence of pollen production and this was assessed in at least two flowers per plant. Individuals with yellow anthers visibly releasing pollen were scored as 'male-fertile' , whereas plants that produced white vestigial stamens and whose anther sacs lacked pollen were scored as 'male-sterile' .…”
Section: Sex Expression and Phenotype Datamentioning
confidence: 99%
See 2 more Smart Citations
“…As in previous studies (Goldberg et al, 2010;Spigler et al, 2010), we scored male function qualitatively based on the presence or absence of pollen production and this was assessed in at least two flowers per plant. Individuals with yellow anthers visibly releasing pollen were scored as 'male-fertile' , whereas plants that produced white vestigial stamens and whose anther sacs lacked pollen were scored as 'male-sterile' .…”
Section: Sex Expression and Phenotype Datamentioning
confidence: 99%
“…Both parental species show gender dimorphism and sexual dimorphism in secondary traits (Ashman, 2003(Ashman, , 2005Ashman et al, 2011; but they differ in the chromosome that houses the sex-determining region (Goldberg et al, 2010). F. chiloensis is predominantly dioecious (Hancock and Bringhurst, 1979b) and recent mapping studies have revealed that sex is determined by a dominant sterility allele (A) at the male function 'locus' and recessive sterility allele (g) at the female function 'locus' and that these 'loci' colocalize on linkage group (LG) VI.A (Goldberg et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, all F. × ananassa maps were built on F1 progeny obtained from inter/intraspecific cross pollination (CP) of highly heterozygous cultivars (Haymes et al 1997;Lerceteau-Köhler et al 2003, 2012Rousseau-Gueutin et al 2008;Sargent et al 2009Sargent et al , 2012Goldberg et al 2010;Isobe et al 2012;Gaston et al 2013;van Dijk et al 2014;Mohamed 2014).…”
Section: Speciesmentioning
confidence: 99%
“…Since more abundant progeny carries a greater number of meiotic recombination events, thus, it determines the resolution and accuracy of the linkage map more precisely (Paterson 1996), larger segregating populations of over 100 individuals were introduced in the study on F. vesca (Koskela et al 2012), F. virginiana and F. chiloensis (Spigler et al 2008Goldberg et al 2010) as well as F. × ananassa (Lerceteau-Köhler et al 2003, 2012Rousseau-Gueutin et al 2008Weebadde et al 2008;Sargent et al 2009Isobe et al 2012;Gaston et al 2013;van Dijk et al 2014). Nevertheless, as some economic factors may limit the progeny number, the bin (selective) mapping appears to be a strategy of choice (Vision et al 2000).…”
Section: Speciesmentioning
confidence: 99%